Penampilan Pertumbuhan Jeruk Besar (Citrus grandis (L.) Osbeck) cv. Cikoneng pada Beberapa lnterstock - Slamet Susanto; Ketty Suketi; , Mukhlas; Lia Rachmawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
The purpose of the research was to study the growth performance of pummelo cv. Cikoneng grafted on several interstocks. Four interstock cultivars i.e. Flying Dragon (Poncirus trifoliata Var. Monstrosa), Troyer (Poncirus trifoliata x Citrus sinensis), Citrumelo (Citrus paradisi x Poncirus trifoliata) and Rangpur Lime (Citrus limonia Os beck x Troyer Citrange) weres ubjectedt o this experiment.A ll interstocksw ereg rafted on JapanscheC itroen rootstock.The experiment was arranged in a Randomized Block Design. All seedlings grew normal, no incompatibility symptom between scion and interstocks was observed. Rangpur Lime interstock tended to retard scion growth, inversely, Citrumelo interstock was the most promoted scion growth. Flying Dragon and Troyer had intermediate characteristic, their effect on scion growth was between Rangpur Lime andCitrumelo. Key words: Pummelo, Cikoneng, lnterstock